Using of the organizational network analysis to build competitiveness on the example of enterprise energy sector = Wykorzystanie analizy sieci organizacyjnej w budowaniu konkurencyjności na przykładzie przedsiębiorstw branży energetycznej - Wawrzynek, Łukasz (Zielona Góra: Faculty of Economics and Management Press)
Contemporary organizations operate in dynamic, complex markets. One of the directions of their development is the increase of competitiveness level. This level must be based on factors for building competitive advantage, clear for the given organization, or, in a broader sense, based on general conditions for the increase of competitiveness. One of these directions could be innovation, which would lead to development and the gaining of new markets. Being innovative depends on the ideas and their implementation.
Keywords: analiza sieci organizacyjnych; konkurencyjność; innowacyjność; pracownicy; potencjał; organizational network analysis; competitiveness; innovation; key players; potential